ANÁLISE DA SOBREPOSIÇÃO DE NICHO ECOLÓGICO DO LOBO-GUARÁ (CHRYSOCYON BRACHYURUS, ILLIGER, 1815), UM DISPERSOR ESPECÍFICO DA PLANTA LOBEIRA (SOLANUM LYCOCARPUM A. ST.) NO BIOMA CERRADO - Henrique Silvestre Cardinal , Renan; Gabriel Andreio Cabrera, Pedro; Fernanda de Oliveira, Samara; Vieira , Eliane; Pontara , Vanessa; Leandro Bueno , Marcelo (ANAIS DO ENIC, 2026)
-